2018
DOI: 10.1007/s00436-018-5755-4
|View full text |Cite
|
Sign up to set email alerts
|

A new flesh fly species (Diptera: Sarcophagidae) parasitic on leptodactylid frogs

Abstract: Here we describe a new species of sarcophagid fly reared from larvae found feeding on three species of leptodactylid frogs collected in subtropical Corrientes Province in northeastern Argentina. Our species description is based on adult male and female external morphology and genitalia. Adult males and females of the new species were associated with certainty because all specimens studied were reared from single clutches of larvae on each of three infested frogs. Thus, adult males and females reared from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Attademo et al (2018: 633, their Table 1); Ghirardi et al (2018: 216–218, 220, their Figs. 1–3, their Table 1); Huttemann and Lavilla (2018: their Table 1); Jetz and Pyron (2018: their supplementary information); Mageski et al (2018: 248); Mulieri et al (2018: 810, 813, 817, their Figs. 22–23); Pesci et al (2018: their Table 1); Baldo et al (2019: 20); Catalano et al (2021: 635); Curi et al (2019: 1–3, 5–6, 8–10, their Figs.…”
Section: Species Accountsmentioning
confidence: 99%
“…Attademo et al (2018: 633, their Table 1); Ghirardi et al (2018: 216–218, 220, their Figs. 1–3, their Table 1); Huttemann and Lavilla (2018: their Table 1); Jetz and Pyron (2018: their supplementary information); Mageski et al (2018: 248); Mulieri et al (2018: 810, 813, 817, their Figs. 22–23); Pesci et al (2018: their Table 1); Baldo et al (2019: 20); Catalano et al (2021: 635); Curi et al (2019: 1–3, 5–6, 8–10, their Figs.…”
Section: Species Accountsmentioning
confidence: 99%
“…Evolution of sarcophagid life histories and male terminalia traits Since I was interested in the evolutionary trajectory of life histories and male terminalia in the subfamily Sarcophaginae, I inferred ancestral character states using the dated phylogeny. Biological data were compiled mostly from the literature (3,4,72,(162)(163)(164)(165)(166)(73)(74)(75)(76)(77)(78)(79)(80)(81)5,(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)6,(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)9,(102)(103)(104)(105)(106)(107)(108)(109)…”
Section: Diversi Cation Rate Estimationmentioning
confidence: 99%
“…stenocotyle (Cohn, 1902) (metacercariae) (Hamann and González 2009). Mulieri et al (2018) reported the presence of an ectoparasitethe larvae of the sarcophagid fly, Lepidodexia (Notochaeta) adelina Mulieri, Schaefer, Duré and González, 2018-in this species. We report three novel parasites in a Physalaemus albonotatus collected in Corrientes (Argentina)-viz., a nematode larva of the order Rhabditida in the eye, and cystacanths and cosmocercids in the mesentery and the large intestine, respectively. On the morning of 06 December 2017, one of authors (EFS) captured a female P. albonotatus (Figure 1 A, B) in the 8-ha compound of the Centro de Ecología Aplicada del Litoral (CECOAL); this fi eld station in the suburbs of the city of Corrientes (27°29'33.89" S, 58°45'33.63" W) is operated by the Consejo Nacional de Investigaciones Científi cas y Técnicas (CONICET) of Argentina.…”
mentioning
confidence: 95%